The impact of peer solution quality on peer-feedback provision on geometry proofs: Evidence from eye-movement analysis. (December 2018) - Alqassab, Maryam; Strijbos, Jan-Willem; Ufer, Stefan
Abstract: Providing feedback on peer solutions to geometry proofs can support preservice mathematics teachers' assessment skills of such complex tasks. However, the quality of peer solutions may influence cognitive processing during peer-feedback provision, learning from providing peer-feedback, and peer-feedback content. To investigate this effect, we recorded the eye-movements of fifty-three preservice mathematics teachers while providing feedback on a near-correct or an erroneous peer solution to a geometry proof, and we measured their proof comprehension and peer-feedback content. Results show that the absence of errors earlier in the peer solution facilitated reliance on a figure-based approach, whereas encountering errors earlier in the peer solution was associated with more focus on the text of the proof. Students who provided peer-feedback on the near-correct peer solution had better comprehension of the proof, and they provided more accurate peer-feedback. Errors in peer solutions thus appear to hinder positive peer-feedback outcomes. Highlights: Peer solution quality influences cognitive processing in peer-feedback provision. Erroneous peer solutions hinder proof comprehension of peer-feedback providers. Peer-feedback on an erroneous peer solution to a geometry proof is less accurate.